2015
DOI: 10.1890/15-0440.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring spatial variation in secondary production and food quality using a common consumer approach in Lake Erie

Abstract: Lake Erie is a large lake straddling the border of the USA and Canada that has become increasingly eutrophic in recent years. Eutrophication is particularly focused in the shallow western basin. The western basin of Lake Erie is hydrodynamically similar to a large estuary, with riverine inputs from the Detroit and Maumee Rivers mixing together and creating gradients in chemical and physical conditions. This study was driven by two questions: (1) How does secondary production and food quality for consumers vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 45 publications
(63 reference statements)
3
19
0
Order By: Relevance
“…Length is the maximum anterior‐to‐posterior dimension of the shell measured roughly parallel to the hinge; width is the maximum left–right dimension with both valves appressed; height is the maximum dorsal‐ventral dimension of the shell measured roughly perpendicular to the hinge. As previously reported, in 2013 sometimes mussels grew in atypical shapes due to crowding in the cages (Larson et al ), this did not occur in other years. For this reason, we did not use length as our index of growth, but instead report change in nominal volume (length × width × height) on a per‐day basis.…”
Section: Methodssupporting
confidence: 71%
See 4 more Smart Citations
“…Length is the maximum anterior‐to‐posterior dimension of the shell measured roughly parallel to the hinge; width is the maximum left–right dimension with both valves appressed; height is the maximum dorsal‐ventral dimension of the shell measured roughly perpendicular to the hinge. As previously reported, in 2013 sometimes mussels grew in atypical shapes due to crowding in the cages (Larson et al ), this did not occur in other years. For this reason, we did not use length as our index of growth, but instead report change in nominal volume (length × width × height) on a per‐day basis.…”
Section: Methodssupporting
confidence: 71%
“…Mussel cages used in this study are identical to those previously reported in Larson et al () and Larson et al (). Briefly, mussel cages were made using plastic‐coated mesh with diamond‐shaped openings that have a maximum width of 1.4 cm.…”
Section: Methodsmentioning
confidence: 52%
See 3 more Smart Citations